Association mapping for cold tolerance in two large maize inbred panels. Issue 1 (December 2016) - Revilla, Pedro; Rodríguez, Víctor; Ordás, Amando; Rincent, Renaud; Charcosset, Alain; Giauffret, Catherine; Melchinger, Albrecht; Schön, Chris-Carolin; Bauer, Eva; Altmann, Thomas; Brunel, Dominique; Moreno-González, Jesús; et al.
Abstract Background Breeding for cold tolerance in maize promises to allow increasing growth area and production in temperate zones. The objective of this research was to conduct genome-wide association analyses (GWAS) in temperate maize inbred lines and to find strategies for pyramiding genes for cold tolerance. Two panels of 306 dent and 292 European flint maize inbred lines were evaluatedper se and in testcrosses under cold and control conditions in a growth chamber. We recorded indirect measures for cold tolerance as the traits number of days from sowing to emergence, relative leaf chlorophyll content or quantum efficiency of photosystem II. Association mapping for identifying genes associated to cold tolerance in both panels was based on genotyping with 49, 585 genome-wide single nucleotide polymorphism (SNP) markers. Results We found 275 significant associations, most of them in the inbreds evaluatedper se, in the flint panel, and under control conditions. A few candidate genes coincided between the current research and previous reports. A total of 47 flint inbreds harbored the favorable alleles for six significant quantitative trait loci (QTL) detected for inbredsper se evaluated under cold conditions, four of them had also the favorable alleles for the main QTL detected from the testcrosses. Only four dent inbreds (EZ47, F924, NK807 and PHJ40) harbored the favorable alleles for three main QTL detected from the evaluation of the dent inbredsper se under cold conditions. There were more QTL in the flint panel and most of the QTL were associated with days to emergence and ΦPSII. Conclusions These results open new possibilities to genetically improve cold tolerance either with genome-wide selection or with marker assisted selection.